A fusion protein of interleukin‐4 and interleukin‐10 protects against blood‐induced cartilage damage in vitro and in vivo. (17th August 2017) - van Vulpen, L. F. D.; Popov‐Celeketic, J.; van Meegeren, M. E. R.; Coeleveld, K.; van Laar, J. M.; Hack, C. E.; Schutgens, R. E. G.; Mastbergen, S. C.; Lafeber, F. P. J. G.
Abstract : Essentials Targeted treatment for hemophilic arthropathy, still causing significant morbidity, is lacking. This study evaluates the efficacy of a fusion of protein of interleukin(IL)‐4 and IL‐10. In vitro the fusion protein prevents blood‐induced cartilage damage in a dose‐dependent manner. In hemophilic mice, the IL4‐10 fusion protein ameliorates cartilage damage upon joint bleeding. Summary: Background: Joint damage still causes significant morbidity in hemophilia. It results from synovial inflammation and direct cartilage‐degenerating properties of blood components. Interleukin (IL)‐4 and IL‐10 have been shown to protect cartilage from blood‐induced damage. Recently an IL4‐10 fusion protein has been developed to combine the function of IL‐4 and IL‐10 and increase their bioavailability. Objectives: In this study we evaluate whether this IL4‐10 fusion protein protects against blood‐induced joint damage. Methods: In vitro, human cartilage explants were exposed to whole blood and simultaneously to a broad concentration range of the IL4‐10 fusion protein. Effects on cartilage matrix turnover were compared with the individual cytokines. Moreover, the influence of the fusion protein and its individual components on IL‐1β and IL‐6 production was investigated. In hemophilia A mice, the effect of intra‐articular treatment on synovitis and cartilage damage resulting from joint bleeding was evaluated by histochemistry. Results: In vitro, the fusion protein prevented blood‐induced cartilage damage in a dose‐dependent manner, with equal effectiveness to the combination of the separate cytokines. In whole blood cultures 10 ng mL −1 fusion protein completely blocked the production of IL‐1β and IL‐6 by monocytes/macrophages. In hemophilic mice, intra‐articular injection of IL‐4 and IL‐10 did not influence synovitis or cartilage degeneration. In contrast, equimolar amounts of the fusion protein attenuated cartilage damage upon repeated joint bleeding, although synovial inflammation was hardly affected. Conclusions: Overall, this study shows that the IL4‐10 fusion protein prevents blood‐induced cartilage damage in vitro and ameliorates cartilage degeneration upon joint bleeding in hemophilic mice.